The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1590/s0103-50532013000100003
|View full text |Cite
|
Sign up to set email alerts
|

A new approach for the synthesis of 3-substituted cytotoxic nor-β-lapachones

Abstract: Vários estudos têm mostrado o potencial citotóxico de derivados da nor-β-lapachona contra células tumorais. Considerando a nor-β-lapachona um importante protótipo, uma série inédita de nor-β-lapachonas substituídas em C-3 foi sintetizada através de uma nova metodologia sintética envolvendo intermediário sintético 3-hidróxi-nor-β-lapachona para o acoplamento de alguns nucleófilos contendo núcleos derivados de carboidratos ou 2H-pirazóis. Todos os derivados foram avaliados frente a quatro linhagens de células tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…(synon. Tabebuia, Bignoniaceae family) [ 4 ] and first isolated from Tabebuia avellanedae, in 1882 by Paternó [ 5 ], was used as an antiplasmodial drug during World War II, when there was a shortage of quinine, the only available antimalarial agent at that time [ 6 ]. Since the pioneering work of Wendel (1946), who demonstrated that lapachol ( 2 , Figure 1 ) was active against P. vivax [ 7 ], numerous publications reported on the antiplasmodial activity of naphthoquinones leading to the development of atovaquone ( 3 , Figure 1 ), a totally synthetic hydroxy-1,4-naphthoquinone [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…(synon. Tabebuia, Bignoniaceae family) [ 4 ] and first isolated from Tabebuia avellanedae, in 1882 by Paternó [ 5 ], was used as an antiplasmodial drug during World War II, when there was a shortage of quinine, the only available antimalarial agent at that time [ 6 ]. Since the pioneering work of Wendel (1946), who demonstrated that lapachol ( 2 , Figure 1 ) was active against P. vivax [ 7 ], numerous publications reported on the antiplasmodial activity of naphthoquinones leading to the development of atovaquone ( 3 , Figure 1 ), a totally synthetic hydroxy-1,4-naphthoquinone [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…This compound has been the basis for the synthesis of several important analogues or derivatives with improved biological activities [ 12 , 13 , 14 , 15 , 16 , 17 ]. Recently, it was demonstrated that the modification of the dihydrofuran ring of nor-β-lapachone ( 1 ) could considerably change its activity against cancer cells [ 18 , 19 , 20 , 21 ], Trypanosoma cruzi ( T. cruzi ) [ 22 , 23 , 24 , 25 , 26 ], and candidal agents [ 27 ]. Indeed, the triazolyl series of compounds 2 and the arylamine group of compounds 3 are very active against some cancer cell lines and T. cruzi , respectively ( Figure 1 ).…”
Section: Introductionmentioning
confidence: 99%
“…9 Lately, diverse lapachone derivatives have been reported as potent cytotoxic drugs against different cancer cell lines. 10 In this regard, advances in the synthesis of lapachones with potent antitumor activity have been accomplished via modification of the A-and C-rings, 11 with recent progress being achieved by da Silva Júnior, 12 Pinto, 13 Hong, 14 Ferreira, 15 Bonifazi,16 among others 17 (Scheme 1A).…”
mentioning
confidence: 99%